Measurement Of Organizational Citizenship Behavior (OCB): Transformational Leadership Style, Organizational Culture And Work Motivation - Widowati, Retno; Ismail, Dingot Hamonangan; Hermawan, Eric (International Publisher, 2023)
Organizational Citizenship Behavior (OCB) is proven to have a significant effect on organizational performance and productivity. Because of that there is a lot of research on OCB including what variables contribute to the development of OCB. This study focuses on 3 variables that influence OCB. This study uses a descriptive qualitative research method with a literature study approach where the results show that there is an influence of Transformative Leadership Style, Organizational Culture and Work Motivation on OCB.